Ileosigmoid knot: a case report and literature review of 280 cases - Machado, Norman O. (Medknow Publications, 2009)
Ileosigmoid knotting, also known as compound volvulus or double volvulus, is a rare cause of intestinal obstruction. In this condition the ileum wraps around the base of the sigmoid colon and forms a knot. Ileosigmoid knotting is an unusual entity in the West, but is comparatively common in certain African, Asian and Middle Eastern nations. The condition is serious, generally progressing rapidly to gangrene. Awareness of the condition is essential for prompt diagnosis and optimal management. This report describes a case in a 60-year-old male and describes the management of this rare condition. An additional 280 recent cases in the English literature are reviewed as to etiopathogenesis, presentation, diagnostic modalities, surgical interventions and outcome.